Analisis Determinan Kesehatan Terhadap Kepatuhan Pemakaian Alat Pelindung Diri (Proteksi Radiasi) Bagi Radiografer di Wilayah Pasuruan Dan Sidoarjo - Handi Sumarsono; Nur Wijayanti; Siti Masrochah (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Hospitals in Pasuruan and Sidoarjo are Covid-19 referral hospitals that are very at risk of occupational infections for officers. Radiographer are workers who have more direct contact with patients, therefore nurses must apply the use of Personal Protective Equipment (APD) following the Standard Operating Procedure (SOP). The purpose of the study was to analyze the influence of health determinants (supervision, self-efficacy, and work culture) on compliance with the use of personal protective equipment (radiation protection) for radiographers in the Pasuruan and Sidoarjo regions.Methods: Design observational research with a cross-sectional approach. The population of all radiographers in the Pasuruan and Sidoarjo is 100 people. Sampled all 100 radiographers with total sampling techniques. Independent variables of supervision, self-efficacy, and work culture. Variable dependent compliance with the use of personal protective equipment (radiation protection) for radiographers.Results: The results showed there was an influence of radiographer surveillance patterns on compliance with the use of personal protective equipment (radiation protection) for radiographers (p-value 0.000), there was an effect of radiographer self-efficacy on compliance with the use of personal protective equipment (radiation protection) for radiographers (p-value 0.000), there was the influence of radiographer work culture on compliance with the use of personal protective equipment (radiation protection) for radiographers (p-value 0.000).Conclusions: Supervision, self-efficacy, and work culture are among the factors that significantly influence radiographer adherence to the use of PPE. The hope is that by having a good knowledge of K3, nurses will be more obedient to protection as prevention of infection transmission.